PENGEMBANGAN PROGRAM APLIKASI PERMAINAN BAHASA TEKA-TEKI SILANG KOMPUTER MENGGUNAKAN TURBO PASCAL 5.5 - Sukmono Bayu Adhi (Yayasan Akrab Pekanbaru, 2019)
The purpose of this study is to find out the process of making software that can be used for entertainment media as well as learning media to improve vocabulary in both Indonesian and other foreign languages. The program created is an application program in the form of a crossword puzzle (TTS) game in which the program is titled ‘Teka-Teki Silang Komputer’ (Computer Cross Puzzle). The name means that the crossword puzzle is an application program that can only be played on computers, especially those with DOS operating systems. With this program it is hoped that it can help students or anyone interested in increasing knowledge, especially in the field of vocabulary. Thus the program has a dual benefit, in addition to being an attractive and challenging way to fill leisure time, this program can also help improve language skills by increasing vocabulary. This program consists of several menus where the first menu is the main game consisting of 6 types of shapes or pictures of TTS boxes. On this menu each type consists of 7 levels. While the second menu also consists of 6 kinds of TTS box images but the questions and answers are still empty. This menu is provided for the users who want to make their own questions and answers according to their own wishes using the 6 types of TTS boxes that have been provided. This program can automatically check whether the answer is correct or still incorrect.